1998
DOI: 10.1080/17450399809381931
|View full text |Cite
|
Sign up to set email alerts
|

Research note: Investigation on the metabolism of glycerol in the rumen of bulls

Abstract: Two bulls, each fitted with rumen and duodenal cannulas, received (in addition to a hay-grain diet) twice daily an infusion of 200 g glycerol into the rumen over a period of six days. During this preliminary in vivo investigation, the influence of a glycerol application on the rumen environment over a six-day adaptation period was examined. Samples of rumen fluid were collected daily, two hours after glycerol infusion. An additional 15N-urea application into the rumen was given on days 1 (without glycerol infu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
38
2
8

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(56 citation statements)
references
References 9 publications
7
38
2
8
Order By: Relevance
“…The retention of glycerol within the rumen will depend on the absorption as well as the microbial fermentation and fluid passage rate of this compound. The observed effects of glycerol on ruminal VFA accumulations (Donkin and Doane 2007;Kijora et al, 1998) suggest that glycerol is not absorbed so fast as to preclude appreciable microbial fermentation. These finding suggests that long-term feeding of glycerol may ultimately select and enrich the populations of glycerol-fermenting microbes such as Megasphaera elsdenii and Selenomonas rumiantium.…”
Section: Resultsmentioning
confidence: 88%
“…The retention of glycerol within the rumen will depend on the absorption as well as the microbial fermentation and fluid passage rate of this compound. The observed effects of glycerol on ruminal VFA accumulations (Donkin and Doane 2007;Kijora et al, 1998) suggest that glycerol is not absorbed so fast as to preclude appreciable microbial fermentation. These finding suggests that long-term feeding of glycerol may ultimately select and enrich the populations of glycerol-fermenting microbes such as Megasphaera elsdenii and Selenomonas rumiantium.…”
Section: Resultsmentioning
confidence: 88%
“…This was not observed in the present trial. However, other studies found that glycerol supplementation decreased rumen pH (Kijora et al, 1998;Mach et al, 2009;Wang et al, 2009b). One reason for these seemingly contradictory findings could have been the high content of starch in the maize silage that was fed in these other studies, which is known to decrease the rumen pH.…”
Section: Discussionmentioning
confidence: 85%
“…Similarly, Chung et al (2007) reported that feeding glycerol to dairy cows increased circulatory glucose concentrations. In ruminants, glycerol can be rapidly converted to propionic acid and readily absorbed through the ruminal wall (Johns, 1953; Kijora et al, 1998). Therefore, the glycerol component can be converted to glucose by the liver and kidneys (Krebs and Lund, 1966) to provide energy for cellular metabolism.…”
Section: Resultsmentioning
confidence: 99%